The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1083/jcb.201703152
|View full text |Cite
|
Sign up to set email alerts
|

Structural plasticity of the living kinetochore

Abstract: Dhatchinamoorthy et al. use calibrated imaging, FRAP, and photoconversion to study the changes in kinetochore component copy numbers from G1 to anaphase and find that the Dam1 submodule is unchanged during anaphase, whereas MIND and Ndc80 submodules add copies, providing insight into the dynamics and plasticity of the kinetochore structure during chromosome segregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
63
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 83 publications
14
63
0
Order By: Relevance
“…If two Cse4 molecules are in the nucleosome, presumably two Okp1/Ame1 entities are bound, raising the question of the stoichiometry of other Ctf19 components relative to Okp1/Ame1. Of note, Okp1 and Ame1 are more abundant in the nucleus than Ctf19 and Mcm21 (Dhatchinamoorthy et al, 2017), arguing that not all cellular Okp1/Ame1 is part of COMA. Thus, further work is required to elucidate the precise architecture of the kinetochore at its interface with chromatin.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…If two Cse4 molecules are in the nucleosome, presumably two Okp1/Ame1 entities are bound, raising the question of the stoichiometry of other Ctf19 components relative to Okp1/Ame1. Of note, Okp1 and Ame1 are more abundant in the nucleus than Ctf19 and Mcm21 (Dhatchinamoorthy et al, 2017), arguing that not all cellular Okp1/Ame1 is part of COMA. Thus, further work is required to elucidate the precise architecture of the kinetochore at its interface with chromatin.…”
Section: Discussionmentioning
confidence: 95%
“…The Cse4 content has been proposed to oscillate during mitosis from one to two molecules per centromeric nucleosome (Shivaraju et al, 2012), whereas another study observed replacement of Cse4 during S-phase, and it remained stably present at the centromere for the rest of the cell cycle until the next S-phase (Wisniewski et al, 2014). Of note, Okp1 and Ame1 are more abundant in the nucleus than Ctf19 and Mcm21 (Dhatchinamoorthy et al, 2017), arguing that not all cellular Okp1/Ame1 is part of COMA. Of note, Okp1 and Ame1 are more abundant in the nucleus than Ctf19 and Mcm21 (Dhatchinamoorthy et al, 2017), arguing that not all cellular Okp1/Ame1 is part of COMA.…”
Section: Discussionmentioning
confidence: 98%
“…The outer kinetochore forms the primary MT attachment site for the chromosomes through the KMN (or in yeast, MIND) networks/complexes [21,108,[166][167][168][169][170]. This network/complex contains the Ndc80, KNL1, Mis12, and Dam/DASH proteins/complexes, and is also important for kinetochore signaling and lost kinetochore recapture [77,110,171]. Chromosomes and kinetochores also contain Aurora B kinase (Ark1 in S. pombe), an essential spindle checkpoint component.…”
Section: A16 Chromosomesmentioning
confidence: 99%
“…For example, chromosome misalignment generates a signal that causes the DNA-bound kinetochore assembly platform to solidify while weakening the connection between the microtubule and its interacting proteins (Akiyoshi et al, 2013;Cheeseman et al, 2006;DeLuca et al, 2006;Kim and Yu, 2015;Pinsky et al, 2006). During anaphase, when microtubules pull sister chromatids to opposite spindle poles, outer kinetochore proteins are enriched, ensuring a persistent connection to the depolymerizing filament (Dhatchinamoorthy et al, 2017;Gascoigne and Cheeseman, 2013).…”
Section: Introductionmentioning
confidence: 99%